2020
DOI: 10.3390/molecules25020380
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Volatiles in Different Jasmine Tea Grade Samples Using Electronic Nose and Automatic Thermal Desorption-Gas Chromatography-Mass Spectrometry Followed by Multivariate Statistical Analysis

Abstract: Chinese jasmine tea is a type of flower-scented tea, which is produced by mixing green tea with the Jasminum sambac flower repeatedly. Both the total amount and composition of volatiles absorbed from the Jasminum sambac flower are mostly responsible for its sensory quality grade. This study aims to compare volatile organic compound (VOC) differences in authoritative jasmine tea grade samples. Automatic thermal desorption-gas-chromatography-mass spectrometry (ATD-GC-MS) and electronic nose (E-nose), followed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 38 publications
3
18
0
Order By: Relevance
“…In addition, ( Z )‐jasmone is a principal contributor to the floral odor of green tea, 40 and exhibits a jasmine‐like odor 41 . In this study, α‐farnesene, ( Z )‐jasmone, ( E )‐nerolidol and hotrienol were evaluated as key aromatic components and were found to contribute significantly to the floral aroma of Congou black tea; this result is similar to those in the published literature 10,40,42,43 . Phenylacetonitrile was used to mimic a floral scent 21 .…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…In addition, ( Z )‐jasmone is a principal contributor to the floral odor of green tea, 40 and exhibits a jasmine‐like odor 41 . In this study, α‐farnesene, ( Z )‐jasmone, ( E )‐nerolidol and hotrienol were evaluated as key aromatic components and were found to contribute significantly to the floral aroma of Congou black tea; this result is similar to those in the published literature 10,40,42,43 . Phenylacetonitrile was used to mimic a floral scent 21 .…”
Section: Resultssupporting
confidence: 80%
“…Some compounds, such as ( E )‐caryophyllene (woody–spicy and clove‐like), 44 α‐bergamotene (citrus), 18 propanal (fresh, fruity, and malty), 18 ( E )‐2‐nonenal (cucumber‐like, fatty, and green) 24 and 6‐methyl‐5‐hepten‐2‐one (tomato‐like), 45 provided nonfloral flavors; and other compounds, such as 2,5‐dimethylbenzaldehyde, ( Z )‐3‐hexenyl isovalerate and 2,2,4‐trimethyl‐1,3‐pentanediol diisobutyrate, had no notable flavor; they were also likely to enhance the floral aroma of tea, which may be due to the complex perceptual interactions among volatiles. Other compounds have been reported to contribute toward the floral scents of tea, including linalool, ( Z )‐3‐hexenyl benzoate, and β‐ionone 10,42 . These substances were not identified as key aroma compounds in this experiment because their VIP scores from the OPLS‐DA analyses were low.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…This might be due to the influence of the properties of different compounds and the olfactory threshold. Many studies have shown that various volatile compounds have different degrees of correlation with different E-nose sensors [ 50 , 51 ]. Herein, the differences among the volatile profiles of Hedychium accessions were observed.…”
Section: Discussionmentioning
confidence: 99%
“…Mass spectra were obtained by automatic scanning at m/z 20 to 500 amu. The identification of compounds was perceived via comparing the mass spectra with NIST 08 at a match factor of ≥80 [ 42 , 51 ]. The data were processed using mass hunter qualitative analysis workflow software (Agilent Technologies Inc., Santa Clara, CA, USA).…”
Section: Methodsmentioning
confidence: 99%